Calvin klein (CK) designer cocktail, new "Speedball" is the "grimm reaper": Brain dopaminergic surge a potential death sentence. Issue 3 (2020) - Gold, Mark S; Cadet, Jean Lud; , David Baron; Badgaiyan, Rajendra D; Blum, Kenneth
No abstract available